2012
DOI: 10.1162/jocn_a_00094
|View full text |Cite
|
Sign up to set email alerts
|

Similarity between Brain Activity at Encoding and Retrieval Predicts Successful Realization of Delayed Intentions

Abstract: Remembering delayed intentions can be highly demanding. Accuracy in laboratory paradigms assessing prospective memory (PM) is typically well below ceiling, and failure to remember intended behaviors after a delay is a common occurrence in everyday life. However, relatively little is known of the potential differences in brain activity that distinguish successful versus unsuccessful PM. In this fMRI study, participants repeatedly encoded, stored, and then had the opportunity to retrieve intended behaviors while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
45
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 46 publications
(60 reference statements)
6
45
0
Order By: Relevance
“…This would be consistent with the stronger effect of offloading on 3-target than 1-target trials. The idea that task-negative regions can play a role in representing the content of delayed intentions is also supported by studies from multivariate pattern analysis of fMRI data, which have consistently shown that task-relevant representational content can be decoded from medial rostral PFC, a prominent node of the task-negative network (Gilbert et al, 2012a;Gilbert, 2011;Momennejad & Haynes, 2012, 2013. These findings are incompatible with the idea that activity in medial rostral PFC is characterized entirely by task-unrelated processes.…”
Section: Discussionmentioning
confidence: 96%
“…This would be consistent with the stronger effect of offloading on 3-target than 1-target trials. The idea that task-negative regions can play a role in representing the content of delayed intentions is also supported by studies from multivariate pattern analysis of fMRI data, which have consistently shown that task-relevant representational content can be decoded from medial rostral PFC, a prominent node of the task-negative network (Gilbert et al, 2012a;Gilbert, 2011;Momennejad & Haynes, 2012, 2013. These findings are incompatible with the idea that activity in medial rostral PFC is characterized entirely by task-unrelated processes.…”
Section: Discussionmentioning
confidence: 96%
“…Our study extends this proposal by finding recruitment of the frontoparietal network during a preparatory decision-making period, separate from spatial attention processes or conflict between competing action plans, both of which are known to recruit the frontoparietal network (Scolari et al, 2015). This interpretation is also in line with other findings showing the involvement of the frontoparietal network when intentions had to be kept in memory before execution, in particular during the storage period Gilbert et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Engaging in such "episodic foresight" (or "episodic future thinking" / "prospection", as it is sometimes known) may result in particularly deep encoding of intended actions, which enhances subsequent memory for those actions relative to actions that one has not imagined performing. In line with this argument, it has been suggested that the chances of actually carrying out a previously formed intention increase when the context the intention is formed and encoded in is similar to the context it will be retrieved in (Gilbert, Armbruster, & Panagiotidi, 2012). Studies have also shown that mentally imagining a visual image actives the neural areas associated with viewing that visual image (see e.g., Stokes et al, 2009).…”
mentioning
confidence: 91%